A nonactivating ITGB3 mutation in the β3 cytoplasmic region causes macrothrombocytopenia with an impaired αIIbβ3/RhoA pathway - Keiichi Nakata; Keigo Akuta; Takaya Endo; Midori Koike; Daisuke Motooka; Daisuke Okuzaki; Hisashi Kato; Yoshiaki Tomiyama; Naoki Hosen; Hirokazu Kashiwagi (Blood Vessels, Thrombosis & Hemostasis)
Abstract: Almost all mutations of ITGA2B or ITGB3 identified in congenital macrothrombocytopenia induce constitutive activation of αIIbβ3. However, whether concomitant αIIbβ3 activation is essential for macrothrombocytopenia development remains unknown. Recently, we identified the β3(R760C) mutation that does not induce αIIbβ3 activation in a patient with macrothrombocytopenia. The family study showed that macrothrombocytopenia with reduced expression of αIIbβ3 and glycoprotein IV (GPVI) appeared to be associated with patients heterozygous for β3(R760C). We generated β3(R760C) knockin (KI) mice and investigated the effects of the mutation on platelet/megakaryote biology. Macrothrombocytopenia was decreased to 76% and 40% of platelet counts in heterozygous (Hetero) and homozygous (Homo) KI mice, respectively, when compared with the wild-type mice. Platelet αIIbβ3 and GPVI expression were decreased in KI mice, and αIIbβ3 activation was not detected in nonstimulated KI platelets. Thus, the hetero KI mice reproduced the phenotype of the human participant, indicating that the β3(R760C) mutation is responsible for the macrothrombocytopenia. Platelet aggregation, agonist-induced JON/A binding, and P-selectin expression were impaired in KI mice. Platelet spreading on fibrinogen was also impaired in Homo mice with adenosine 5′-diphosphate or thrombin stimulation. Filopodia and lamellipodia formation was impaired in fibrinogen-adhered megakaryocytes of Homo mice with significantly impaired RhoA activation. Proplatelet formation in Homo mice was impaired with abnormal morphology. In addition, platelet life span was shortened in Homo mice. These data indicate that the β3(R760C) mutation impairs the inside-out and outside-in signaling of αIIbβ3, and abnormal actin rearrangement and impaired RhoA activation may play major roles in macrothrombocytopenia.